Role of comprehensive cytogenomic investigation in successful reproductive outcome of parental small neocentromeric supernumerary ring chromosome: A case report - Yiming Wang; Joanna Lazier; Diane Myles‐Reid; Abdul Noor; David Chitayat; Elena Greenfeld (Clinical Case Reports, 2023)
Abstract Small supernumerary marker chromosomes (sSMC) can form small supernumerary ring chromosomes (sSRC). Loss of parentally inherited sSRC containing vital gene content may cause an “unbalanced” karyotype and fetal microdeletion syndromes. Rarely, sSRC with neocentromere can be inherited, leading to a “balanced” karyotype, which can be diagnosed with preimplantation genetic testing.